Type-III interferons and rheumatoid arthritis: Correlation between interferon lambda 1 (interleukin 29) and antimutated citrullinated vimentin antibody levels - Diana Castillo-Martínez; Maribel Juarez; Mariana Patlán; Araceli Páez; Felipe Massó; Luis M. Amezcua-Guerra (Autoimmunity, 2017)
Aim: To assess serum type III or lambda (λ) interferons (IFN) levels and its clinical and laboratory associations in rheumatoid arthritis (RA). Methods: A cross-sectional study including 43 patients with RA (86% females; age 45.3 ± 10.3 years) and 43 healthy individuals was performed. Clinical data including disease activity, acute-phase reactants, rheumatoid factor and anticyclic citrullinated peptide (anti-CCP) antibodies were collected. Serum IFNλ1, IFNλ2, IFNλ3, CXCL8 and anti-mutated citrullinated vimentin (anti-MCV) antibody levels were measured. Results: Patients with RA had higher IFNλ1 (113.5 ± 118.6 pg/mL versus 55.9 ± 122.3 pg/mL; p < 0.0001) and IFNλ2 (245.4 ± 327.7 pg/mL versus 5.1 ± 11.0 pg/mL; p = 0.009) levels than controls, but not IFNλ3 levels. Notably, IFNλ1 levels were found to be higher in both patients with active disease (124.9 ± 135.9 pg/mL; p < 0.001) and quiescent disease (99.0 ± 93.7 pg/mL; p < 0.01), while IFNλ2 levels were higher only in patients with active disease (264.0 ± 356.1 pg/mL; p = 0.02). A noteworthy association between serum IFNλ1 levels and anti-MCV antibody titers (Spearman's rho coefficient 0.36, 95% CI 0.36 to 0.61; p = 0.02) was observed. Conclusion: Serum IFNλ1 and IFNλ2 levels are abnormally elevated in patients with RA and the former are linearly associated with circulating anti-MCV antibody levels. These results may place type-III IFN as an attractive new therapeutic target in RA.